Trespasses - Kennedy, Louise (Ph. D.) (New York : Riverhead Books, 2022)
"Set in Northern Ireland during the Troubles, a shattering debut novel about a young woman caught between allegiance to community and unsanctioned love"--
Keywords: Northern Ireland -- History -- 1968-1998 -- Fiction; Historical fiction